2012
DOI: 10.1161/circep.111.962753
|View full text |Cite
|
Sign up to set email alerts
|

Microbiology and Pathogenesis of Cardiovascular Implantable Electronic Device Infections

Abstract: A dvancements in our understanding of cardiac conduction abnormalities and pathophysiology of congestive heart failure coupled with innovations in device manufacturing and programming have helped to create a demand for a plethora of newer cardiovascular devices over the past 3 decades. Appropriate use of cardiovascular implantable electronic devices (CIEDs) in carefully selected patients is associated with better survival and significant improvements in quality of life. 1 Cardiac resynchronization therapy devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 91 publications
1
57
0
Order By: Relevance
“…[1][2][3] Indeed, data collected in 2009 from 61 different countries have shown a continuous rise in the number of cardiac implantable electronic devices (CIEDs) being inserted worldwide, with the highest number of implanted PPMs in the USA (225 567) and Germany accounting for 927 new implants per million population. 4 Although infection following CIED use remains relatively uncommon, it may affect exclusively the generator pocket, intravascular electrode components, or endocardial structures, or may even present in different combinations, making the clinical suspicion often delayed and not considered.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Indeed, data collected in 2009 from 61 different countries have shown a continuous rise in the number of cardiac implantable electronic devices (CIEDs) being inserted worldwide, with the highest number of implanted PPMs in the USA (225 567) and Germany accounting for 927 new implants per million population. 4 Although infection following CIED use remains relatively uncommon, it may affect exclusively the generator pocket, intravascular electrode components, or endocardial structures, or may even present in different combinations, making the clinical suspicion often delayed and not considered.…”
Section: Introductionmentioning
confidence: 99%
“…Staphylococcal species, including both Staphylococcus aureus and coagulase-negative staphylococci, account for the majority of CDIs (7,9); however, unusual organisms (Propionibacterium spp., Corynebacterium spp., Acinetobacter baumannii, Haemophilus influenzae) are also found, and antibiotic resistance is often detected (10)(11)(12)(13). Moreover, there are data indicating that microorganisms can colonize cardiac devices without clinical signs of active infection (14)(15)(16).…”
mentioning
confidence: 99%
“…First, only S. aureus was utilized. For the purpose of this experiment, we sought a species that represented the bulk of clinical infections, grew aggressively, and formed biofilms on prosthetic surfaces [36]. It is possible that the efficacy of PBM(þMR) paste demonstrated in the present study would not have been observed using other organisms also encountered in clinical practice.…”
Section: Discussionmentioning
confidence: 99%